The Xbox/Kinect use in poststroke rehabilitation settings: a systematic review - Túlio Brandão XAVIER-ROCHA; Lara CARNEIRO; Gustavo Celestino MARTINS; Guanis de Barros VILELA-JÚNIOR; Ricardo Pablo PASSOS; Camila Castelo Branco PUPE; Osvaldo José Moreira do NASCIMENTO; Desirée Sant’Ana HAIKAL; Renato Sobral MONTEIRO-JUNIOR (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Active games based on virtual reality have been widely used in the rehabilitation of many clinical conditions. However, studies on the use of Xbox/Kinect are rare, and technology application in stroke treatment is not clear yet. Objective: To verify the outcomes (O) analyzed in randomized controlled trials (C; S) that investigated the use of Xbox/Kinect (I) in patients with stroke (P). Methods: This is a systematic literature review that meets PRISMA standards and the eligibility criteria according to the PICOS strategy. The search procedure was performed by two researchers. The research strategy was repeated in case of divergence. Effect size was calculated by Cohen's formula and Hopkins rank. The risk of individual bias was assessed using PEDro Score and Higgins Classification. Results: The main outcomes were postural balance and activities of daily living, with four studies addressing these variables. However, only one study showed the effect of Xbox/Kinect intervention on balance as large, as in two other studies evaluating manual dexterity and depression, respectively. Conclusion: The greater use of Xbox/Kinect in treating patients after stroke is in recovery of balance and motor function, and the evidence support its application. These findings enable the use of virtual reality technology through Xbox/Kinect in rehabilitation programs, focusing on postural balance and motor skills. However, conclusive results are still not possible. Therefore, caution in the use of this technology is required.